Jednoosobowe spółki Skarbu Państwa. Zagadnienia ustrojowe: [Sole shareholder company of the State Treasury. Systemic issues] (Studia Prawnicze / The Legal Studies, 1995)
Jednoosobowymi spółkami Skarbu Państwa mogą być tylko spółki z o.o. oraz spółki akcyjne. W konsekwencji jednoosobowa spółka Skarbu Państwa jest zawsze osobą prawną w rozumieniu art. 33 k.c.Jednoosobowa spółka Skarbu Państwa może być utworzona tylko w przypadku, w którym przepis zezwala na jej ,,zawiązanie". Przepisami tymi są, z wyjątkiem art. 158 ust. 1 i 2 k.h., przepisy o charakterze szczególnym zawarte bądź w kodeksie handlowym (art. 308 zd. 3) bądź w ustawach szczególnych, z których do najważniejszych należą: ustawa o prywatyzacji przedsiębiorstw państwowych (art. 5, 6 i 16) oraz prawo bankowe (art. 86[2]). Przy tworzeniu jednoosobowych spółek Skarbu Państwa regułą jest decydujący współudział naczelnych organów administracji państwowej (art. 5 ust. 1 i art. 6 ust. 1 ustawy o prywatyzacji przedsiębiorstw państwowych oraz art. 36[2] pkt pr.bank.). Niejednokrotnie jednoosobowe spółki Skarbu Państwa Są tworzone przez akty normatywne (ustawy lub rozporządzenia) zawierające normy o charakterze indywidualnym.Jednoosobowe spółki Skarbu Państwa są właścicielami mienia przydzielonego im w chwili ich utworzenia lub nabyte go później. Mienie to jest mieniem państwowym w rozumieniu art. 44[2] § 1 k.c.Do organów jednoosobowych spółek Skarbu Państwa odnoszą się wprost przepisy kodeksu handlowego o organach spółki z o.o. i spółki akcyjnej, chyba że przepisy szczególne wprowadzają od nich odstępstwa. W praktyce jednak funkcjonowanie organów tych spółek znacznie odbiega od zasad kodeksu handlowego. W charakterze zgromadzenia wspólników oraz walnego zgromadzenia akcjonariuszy występują urzędnicy ministerstw, którym dana jednoosobowa spółka Skarbu Państwa jest podporządkowana ze względów branżowych. Ministerstwa niejednokrotnie ingerują w bieżącą działalność jednoosobowych spółek Skarbu Państwa bądź bezpośrednio jako przedstawiciele jedynego akcjonariusza pod postacią zgromadzenia wspólników lub walnego zgromadzenia akcjonariuszy, bądź przez całkowicie od nich zależne rady nadzorcze. Ingerencje te w praktyce bardzo ograniczają samodzielność jednoosobowych spółek Skarbu Państwa, a w konsekwencji ich odrębność od Skarbu Państwa i innych państwowych osób prawnych. Prowadzi to do ponownego skupienia w ręku rządowych organów administracji gospodarczej funkcji imperium i funkcji dominium.Jednoosobowe spółki Skarbu Państwa najczęściej powstają w wyniku komercjalizacji, tj. przekształcenia przedsiębiorstwa państwowego lub innej państwowej osoby prawnej, np. banku państwowego, w spółkę. Z założenia miałoby to stanowić pierwszy krok do późniejszej prywatyzacji tej spółki. Prywatyzacja powinna nastąpić w stosunkowo krótkim terminie, określonym ustawowo. W praktyce terminy te często nie są dotrzymywane. Forma prawna jednoosobowych spółek Skarbu Państwa, zamiast mieć charakter przejściowy, zaczyna stawać się także formą trwałą; jednoosobowe spółki Skarbu Państwa tworzone poza procesem prywatyzacji są najczęściej ich docelową formą prawną, a w każdym razie nie przewiduje się ich rychłej prywatyzacji. Zauważyć wreszcie można próby wykorzystywania formy jednoosobowych spółek Skarbu Państwa do etatyzacji jednostek państwowych uprzednio skomercjalizowanych.Zamierzenia takie należy uznać, za sprzeczne z dążeniem do rozwijania w Polsce gospodarki wolnorynkowej. Only limited liability companies and joint stock companies can be sole shareholder companies of the State Treasury. Consequently, the sole shareholder company of the State Treasury is always a legal entity within the meaning of Article 33 of the Civil Code.The sole shareholder company of the State Treasury may only be established where a provision allows it to be “incorporated”. These provisions are, with the exception of Article 158(1) and (2) of the Commercial Code, provisions of a special nature contained either in the Commercial Code (Article 308 sentence 3) or in special acts, the most important of which are the Acts on Privatisation of State Enterprises (Articles 5, 6 and 16) and the Banking Law (Article 86[2]). When establishing sole shareholder companies of the State Treasury, the rule is decisive participation of the chief bodies of state administration (Article 5(1) and Article 6(1) of the Act on Privatisation of State Enterprises and Article 36[2] of the Banking Law). Sole shareholder companies of the State Treasury are often created by normative acts (acts or regulations) containing norms of an individual nature.Sole shareholder companies of the State Treasury own the property allocated to them at the time of their establishment or acquired later. This property is state property within the meaning of Article 44[2] § 1 of the Civil Code.The provisions of the Commercial Code on the bodies of a limited liability company and a joint-stock company apply directly to the bodies of sole shareholder companies of the State Treasury, unless special provisions introduce exceptions thereto. In practice, however, the functioning of the bodies of these companies deviates significantly from the principles of the Commercial Code. Officials of the ministries to which the sole shareholder company of the State Treasury in question is subordinated for industry reasons act as the shareholders’ assembly and the general meeting of shareholders. Ministries frequently intervene in the day-to-day operations of the sole shareholder companies of the State Treasury either directly as representatives of the sole shareholder in the form of a shareholders’ meeting or the general meeting of shareholders, or through supervisory boards entirely dependent on them. These interferences in practice severely limit the independence of sole shareholder companies of the State Treasury and, consequently, their separateness from the State Treasury and other state legal entities. This leads to a refocusing of the functions of the empire and the functions of the dominion in the hands of the government economic administration bodies.Sole shareholder companies of the State Treasury are most often established as a result of commercialisation, i.e. the transformation of a state-owned enterprise or other state-owned legal entity, such as a state-owned bank, into a company. By assumption, this would be the first step towards the subsequent privatisation of this company. Privatisation should take place within a relatively short statutory timeframe. In practice, these deadlines are often not met. The legal form of sole shareholder companies of the State Treasury, instead of being temporary, is also beginning to become a permanent form; sole shareholder companies of the State Treasury created outside the privatisation process are most often their target legal form, and in any case their imminent privatisation is not envisaged. Finally, one can note attempts to use the form of sole shareholder companies of the State Treasury to etatisation of previously commercialised state entities.Such intentions should be regarded as contrary to the desire to develop a free market economy in Poland.